A simulation model of the real-world fuel and energy consumption of light-duty vehicles - Zacharof, Nikiforos; Doulgeris, Stylianos; Zafeiriadis, Alexandros; Dimaratos, Athanasios; van Gijlswijk, René; Díaz, Sonsoles; Samaras, Zissis (Frontiers in Future Transportation, 2024)
The European Union has intensified efforts to reduce CO 2 emissions from the transport sector, with the target of reducing tailpipe CO2 emissions from light-duty vehicle new registrations s by 55% by 2030 and achieving zero emissions by 2035 according to the "Fit for 55" package. To promote fuel and energy consumption awareness among users under real-world conditions the MILE21 -LIFE project provided tools such as a self-reporting tool and a find-a-car tool that included the official and representative on-road fuel/energy consumption values. In order to produce representative values, an in-house vehicle longitudinal dynamics simulation model was developed for use in the background of the online platform. The model was validated using measurements from a dedicated testing campaign and performed well for petrol vehicles with an average divergence of -1.1%. However, the model showed a divergence of 9.7% for diesel vehicles, 10.6% for hybrids and 8.7% for plug-in hybrids. The model was also applied to US vehicles and showed a divergence of 1.2% and 10% for city and highway driving, respectively.